Development of a robust and stable mass based spectrometry method for analysis of Alzheimer's disease biomarkers in human cerebrospinal fluid: Biomarkers (non‐neuroimaging) / Method development and/or quality control. (7th December 2020) - Leslie, Shannon N.; Wilson, Rashaun; Trombetta, Bianca A.; Kivisäkk, Pia; Arnold, Steven E.; Nairn, Angus C.; Carlyle, Becky C.
Abstract: Background: Current diagnostic tests for Alzheimer's Disease (AD) rely predominantly on amyloid‐beta and tau measurements. However, these markers are insufficient to predict onset of disease, response to treatment, and do not capture the full spectrum of disease progression. Thus, a more expansive approach to diagnostic markers is required. Given the low abundance of putative proteins of interest in biofluids and the impact of relatively small changes in protein levels on the function of central nervous system, a highly sensitive but broad approach to protein monitoring is essential to identifying more comprehensive biomarkers. Data‐independent acquisition (DIA) mass spectrometry is an important tool for achieving this goal given both breadth and depth of protein analysis it enables. Thus, we developed a DIA method that allows for technically reproducible monitoring of thousands of peptides in human cerebrospinal fluid (CSF) to better characterize effective candidate peptides for the development of future targeted biomarker assays. Method: Human CSF was analyzed via liquid‐chromatography tandem mass spectrometry (LC‐MS) with a data‐independent acquisition (DIA) technique. Stable isotopic peptides, enriched for putative proteins of interest to AD diagnostics, were used to create a heavy peptide standard mix. We characterized the stability and linearity of these peptides for use as a normalization tool. Utilizing this well characterized standard mix, we analyzed 30 samples from 15 patients collected at 2 different sites using DIA LC‐MS. Samples included a variety of disease states as well as longitudinal samples to assess both technical and biotemporal stability of peptides. Result: Our novel heavy peptide standard mix showed strong technical reproducibility and linear coherence with concentration. We were able to minimize and control for technical variation utilizing this standard mix; thus, enabling better cross‐sample comparisons of peptides. We characterized the technical reproducibility and stability of our methodology for thousands of peptides across a variety of technical and biological conditions. Overall, this methodology enables stable characterization of peptides across longitudinal samples and between disease conditions. Conclusion: We have developed a robust approach for stable monitoring of hundreds of proteins in human CSF, an important step toward utilization of novel biomarkers in AD diagnostics.